Soil chemical attributes and organic matter quality in sugarcane harvest systems with and without burning - Signor, Diana; Czycza, Rodrigo Vianei; Milori, Débora Marcondes Bastos Pereira; Cunha, Tony Jarbas Ferreira; Cerri, Carlos Eduardo Pellegrino (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate soil chemical attributes, to quantify soil contents and stocks of C and N, and to evaluate the chemical quality of soil organic matter in sugarcane harvest systems with or without burning. Cultivated sugarcane areas were evaluated with or without burning of the fields at 6 and 12 years after the last renovation of the sugarcane fields. In addition, a native vegetation area and another one cultivated for 19 years without burning were also evaluated. Soil C content in the unburnt areas was higher than that of the burnt ones and lower than that of the areas with native vegetation. Carbon stock at the 0.0–0.3-m soil depth in the burnt areas was 22% lower than in the 6-year unburnt area and 43% lower in the 12-year area. The highest humification degrees occurred in the 19-year unburnt area; and the lowest, in the native vegetation area. The cultivated soils showed higher concentration of phenolic and carboxylic groups in humic acids. Soil fertility increases in the unburnt sugarcane areas because of their more humified organic matter and of the higher quantity of carboxylic and phenolic groups.